QIYAS DALAM PEMIKIRAN IBNU TAIMIYAH - Achmad Sulton Faishol; Yoyo Hambali; Oni Wastoni (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
The purpose of this study is to find out Qiyas in Islamic law and Qiyas in ibn Taimiyah thought. This research method is a qualitative method used so that research activities can be carried out in a directed and rational way to achieve optimal results. The type of research carried out is library research, with the approach used in this study is a normative approach. The result of this research is that the Sahih Qiyas are Qiyas that are in line with the texts, the texts never contradict Qiyas, in the Shari'ah there is no case that contradicts the Qiyas, ijtihad must be carried out correctly, in accordance with standard rules, so that the law produced can be accounted for. From the discussion in the previous chapters it can be said as follows: Qiyas in Islamic law is a solution offered for various legal cases that are not explicitly stated in the arguments in Islamic law sources. In order to fulfill the needs of Islam as a true and perfect teaching, obey the scholars to carry out and carry out everything, as well as judge by law and give everything to Allah and fatwas through everything through fatwas of various levels of ijtihad which are carried out continuously with full sense of responsibility.